Internalisasi Nilai Dasar Humanis Religius dalam Bingkai Islam Anak Sekolah Dasar di SD Islam Terpadu - mukhlisin mukhlisin (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2018)
This research is aimed to describe the implant of basic humanist religious values in integrated Islamic Elementary School - a full day school using the naturalistic qualitative method. Humanist education is a unique, independent, and creative human-human system. The behavior of each person is determined by that person and understands man to the environment and himself, to see man as God's created creature to build human character in values ​​human dignity as the most perfect being. Education that carries the natural competence of the students to inspire the development of the child's life inward. This objective at once confirms that the mission and responsibilities of Islamic education is even harder. In this discussion the type and understanding of Islamic education includes all three, has been growing and developing in Indonesia and has become an integral part of the history and education policy nationally. Researchers desire to popularize religious humanist education, as well as to do the concept that will be developed. With the final hope of this research all is the development of religious humanist education paradigm in the middle of Islamic education system for Islamic Elementary School and after that applied or actualized in learning between teacher and student must be admitted that the practice of Islamic education has been more exclusivist than inclusivity.